2018
DOI: 10.1007/s00701-018-3507-y
|View full text |Cite
|
Sign up to set email alerts
|

Cisterna magna arachnoid membrane suturing decreases incidence of pseudomeningocele formation and incisional CSF leakage

Abstract: Suturing of the arachnoid membrane of the cisterna magna and its further sealing with fibrin adhesive sealant TachoComb® create an additional barrier for preventing cerebrospinal fluid collection in the extradural space. This technique significantly reduces the risk of postoperative pseudomeningocele formation and/or an incisional cerebrospinal fluid leak in patients with midline suboccipital craniotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…After completing all sutures without stretching the arachnoid membrane, the free end of the thread was pulled once along the suture to close the incised edges of arachnoid. 3 However, according to our clinical experiences, we believe that 6-0 or 7-0 sutures might injure the arachnoid membrane. Also, pulling the thread only at the end of suturing might cause arachnoid stretching and microtears.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…After completing all sutures without stretching the arachnoid membrane, the free end of the thread was pulled once along the suture to close the incised edges of arachnoid. 3 However, according to our clinical experiences, we believe that 6-0 or 7-0 sutures might injure the arachnoid membrane. Also, pulling the thread only at the end of suturing might cause arachnoid stretching and microtears.…”
Section: Discussionmentioning
confidence: 81%
“…The authors reported that arachnoid suturing significantly decreased the rate of CSF leakage into the subdural space. In addition, Pitskhelauri et al 3 investigated pseudomeningocele and incisional CSF leakage rates after cisterna magna surgery with arachnoid membrane suturing followed by sealing with fibrin adhesive material. The study enrolled 70 patients, 32 of whom were in the control group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of CSF leakage in the analyzed series varied from 0 to 27% ( 2 , 6 , 22 24 , 26 , 47 ), and the incidence of postoperative meningitis was noted in 0.47% - 20% of the cases ( 2 , 6 , 22 , 26 ).…”
Section: Introductionmentioning
confidence: 94%